Bone Healing with or without Platelet‐Rich Plasma around Four Different Dental Implant Surfaces in Beagle Dogs. (7th January 2013) - Streckbein, Philipp; Kleis, Wilfried; Buch, Rainer S. R.; Hansen, Torsten; Weibrich, Gernot
Abstract Purpose Surface development is one of the major aims in dental implant engineering. Additive application of substances could possibly improve the new bone formation around dental implants. The present study evaluated the bone reaction on four different implant surfaces with or without platelet‐rich plasma (PRP). Materials and Methods Four self‐tapping titanium screw implants (Brånemark MK III [Nobel Biocare, Göteborg, Sweden], Osseotite [3i, Miami, FL, USA], Xive [Densply Friadent, Mannheim, Germany], and Compress [IGfZ eG, Diez, Germany]) with different surfaces were inserted in each hemimandible of 12 female beagle dogs; the implant positions and the application of PRP were randomized. After intravital fluorochrome staining, sacrifices and biopsies harvesting were performed after 6 weeks (five dogs; one dog died before) and 12 weeks (six dogs) and the respective specimens were analyzed. Results The only significant difference in bone remodeling was found for the Compress implants with increased bone formation compared with the Brånemark implants at 12 weeks (sign test, p = .03). Comparing the histological and histomorphometric specimens of all other implant surfaces with respect to peri‐implant bone remodeling and the resulting bone‐implant contact rates (BICRs), no statistically significant differences were seen in the PRP or non‐PRP groups (sign test, all p values ≥ .063). Conclusions This study found no significant differences in the BICR for roughened implant surfaces compared with machined surfaces. In this animal model, the addition of PRP did not demonstrate evidence of faster bone formation or the resulting BICR.